Association between Preoperative Leukocytosis and Pathological Features of Colorectal Cancers - Hajebi, Reza; Ahmadi Amoli, Hadi; Zabihi Mahmoudabadi, Hossein; Rahimpour, Ehsan; Najjari, Khosro; Nazar, Elham (Asian Pacific Journal of Cancer Biology, 2021)
Background: Using hematologic profiles including leukocyte count have been considered as prognostic factor for some cancers. We have been assessed the predictive value of leukocytosis before surgery in colorectal cancers. Methods: This cross-sectional study has been conducted on patients with colorectal cancer who underwent surgery from 2017 to 2019 in Sina hospital, Tehran. The patients were divided in two groups based on high and low leukocyte count before surgery. Results: A total of 84 patients were studied with colorectal cancers including 46 males (55.4%) and 37 females (44.6%) with the average age of 55.2 (± 13.63) years. 36.1% of patients had leukocytosis in laboratory data before surgery. There was a significant association between tumor’s grade and the incidence of leukocytosis before surgery (P <0.001). The existence of leukocytosis is highly associated with poorly differentiated tumor. Also, the relationship between the location of the tumor and leukocytosis was seen which the location was distal, the possibility of leukocytosis decreased significantly (P <0.005). Conclusion: Our findings suggest that the location of the tumor and its degree of tumor differentiation are related with leukocytosis. This current study by considering leukocytosis before surgery aimed to use this variable as a prognostic factor in patients with colorectal cancer alongside with other variables.